Taxonomic notes on the genus Yunohamella Yoshida, 2007 (Araneae, Theridiidae) from China, with two new species - Rui Zhong; Yang Zhong; He Zhang; Jie Liu; Changyong Liu; Kuai Chen; Changhao Hu (ZooKeys)
Four Yunohamella species are reported from Hubei Province, China, including two new species: Y. gutenbergi R. Zhong, J. Liu & Hu, sp. nov. (♂) and Y. mohorovicici R. Zhong, J. Liu & Hu, sp. nov. (♂). Yunohamella jiugongensis (Liu & Zhong, 2023), comb. nov. is transferred from the genus Cryptachaea Archer, 1946, and Y. lyrica (Walckenaer, 1841) is newly recorded from Hubei Province and is considered as a senior synonym of Platnickina mneon (Bösenberg & Strand, 1906).